2009
DOI: 10.1111/j.1600-9657.2009.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between traumatic dental injuries and obesity in Brazilian schoolchildren

Abstract: The aim of this study was to investigate if obesity is associated to the occurrence of dental trauma in the permanent anterior teeth of adolescents from Recife, Brazil. It included a random sample of 1046 boys and girls aged 12 years attending both public and private schools. The sample size was calculated using a 95% confidence interval level; a statistical significance of 5%; and an odds ratio of 1.55. The sample selection was carried out in two stages: first, schools were selected by simple sampling, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 29 publications
3
19
1
5
Order By: Relevance
“…This study did not demonstrate a significant association between TDIs to permanent anterior teeth and obesity among 12-year-old schoolchildren in Jordan (P >0.05). This corroborates with the findings of Soriano et al [6], Ărtun and Al-Azemi [7], and Damé-Teixeira et al [8]. However; other authors supported the opposite.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study did not demonstrate a significant association between TDIs to permanent anterior teeth and obesity among 12-year-old schoolchildren in Jordan (P >0.05). This corroborates with the findings of Soriano et al [6], Ărtun and Al-Azemi [7], and Damé-Teixeira et al [8]. However; other authors supported the opposite.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the possible relationship between obesity and TDIs is still unclear. While two studies considered obesity a risk factor for TDIs [3,4], other studies showed no statistically significant relationship [6-8]. In Jordan, few epidemiological studies are available on TDIs to anterior permanent teeth among schoolchildren [9-11], but none of them has explored the relationship between TDIs and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…A sex-stratified analysis showed that the prevalence of dental trauma was greater in overweight/obese boys than in normal-weight boys. Petti et al (12) and Nicolau et al (26) found that childhood obesity significantly increased the risk of traumatic injury, but subsequent studies showed no association between dental trauma and height/ weight proportions (16,25,27,28). The association of obesity with dental trauma may be explained by obese children's reduced agility and greater likelihood of accidents, whereas normal weight may improve motor skills, thereby reducing the risk of accidental falls or incidents during interaction and play with family and friends.…”
Section: Discussionmentioning
confidence: 99%
“…Foi realizada uma revisão da literatura sobre dados epidemiológicos de TD no Brasil 11,12 , prática esportiva 13,14 e, ainda, conhecimento de profissionais, educadores e cirurgiões-dentistas frente ao TD 15,19 .…”
unclassified
“…Pouquíssimos estudos avaliaram a associação entre obesidade e a prevalência de TD, e seus resultados apresentaram-se não concordantes 11,12 . Neste estudo, também se observou que, com relação ao conhecimento sobre o atendimento do TD, melhor capacitação deve ser oferecida tanto para os cirurgiões dentistas quanto para outros profissionais, como cuidadores e educadores, frequentemente presentes no momento do traumatismo dentário [15][16][17][18][19] .…”
unclassified